No Slack : The Financial Lives of Low-Income Americans - Barr, Michael S. (Book collections on Project MUSE., 2012)
The financial crisis exposed the potentially unsavory results of the interaction between low- and moderate income households and alternative and mainstream financial institutions. Many households were overleveraged or paid high costs for financial services, while others lacked access to useful financial products that can cushion against economic instability. The financial services system is not well designed to serve low- and moderate-income households, leaving them without financial slack: they did not have adequate breathing room for making the financial adjustments that would permit them.